Gamma Tocotrienol Protects Mice From Targeted Thoracic Radiation Injury - Kumar, Vidya P.; Stone, Sasha; Biswas, Shukla; Sharma, Neel; Ghosh, Sanchita P. (Frontiers in Pharmacology, 2020)
Radiation injury will result in multiorgan dysfuntion leading to multiorgan failure. In addition to many factors such as radiation dose, dose rate, the severity of the injury will also depend on organ systems which are exposed. Here, we report the protective property of gamma tocotrienol (GT3) in total as well as partial body irradiation (PBI) model in C3H/HeN male mice. We have carried out PBI by targeting thoracic region (lung-PBI) using Small Animal Radiation Research Platform (SARRP), an X-ray irradiator with capabilities of an image guided irradiation with a variable collimator with minimized exposure to non-targeted tissues and organs. Precise and accurate irradiation of lungs was carried out at either 14 or 16 Gy at an approximate dose rate of 2.6 Gy/ min. Though a low throughput model, it is amenable to changes the field size on the spot. No damage to other non-targeted organs was observed in histopathological evaluation. There was no significant change in peripheral blood counts of irradiated mice in comparison to naïve mice. Femoral bone marrow cells had no damage in irradiated mice. As expected, damage to the targeted tissue was observed in the histopathological evaluation and non-targeted tissue was found normal. Regeneration and increase of cellularity and megakaryocytes on GT3 treatment was compared to significant loss of cellularity in saline group. Peak alveolitis was observed on day 14 post-PBI and protection from alveolitis by GT3 was noted. In irradiated lung tissue, thirty proteins were found to be differentially expressed but modulated by GT3 to reverse the effects of irradiation. We propose that possible mode of action of GT3 could be Angiopoietin 2-Tie2 pathway leading to AKT/ERK pathways resulting in disruption in cell survival/ angiogenesis.